Dystocia Due to Fetal Hydrothorax in a Non-Descript Doe - Prakash, Subramanian; Oviya, Srinivas; Satheshkumar , Soundarapandian; Jayaganthan, Ponnusamy (The Indian Journal of Animal Reproduction, 2026)
Dystocia is a relatively common condition in goats; however, cases resulting from fetal abnormalities are infrequently reported. The current report places a record on dystocia due to fetal hydrothorax and its successful management in a non-descript doe.